First biological data of Ceresa nigripectus [Hemiptera:Membracidae], a common treehopper on alfalfa crops in Argentina - Perez Grosso, Tomas; Conci, Luis Rogelio; Saavedra Pons, Amalia Beatriz; Marino, Ana María; Virla, Eduardo G. (2017)
Alfalfa (Medicago sativa L.; Fabaceae) is essential for argentinean agricultural development, but diseases like “witches´ broom», caused by the ArAWB phytoplasma, are limiting factors for the production of this crop. Insects that visit alfalfa have been poorly studied. The treehopper, Ceresa nigripectus Remes Lenicov (Hemiptera: Membracidae) is very frequent in alfalfa crops; ArAWB was detected in several individuals of this treehopper, but the ability of this species to transmit the pathogen has not yet been demonstrated. The Membracidae family is a poorly studied group in Argentina. No data on the biology of C. nigripectus are available, and therefore the aim of this contribution is to provide information on its behavioral and biological parameters as a first step toward its control. The studies were conducted in the laboratory under controlled conditions. Ceresa nigripectus populations were maintained on healthy alfalfa plants; the treehoppers were checked daily, the occurrence of molts was noted, and diverse aspects of nymphal and adult behavior were also recorded. A life table was built combining the observational data from 7 cohorts. Oviposition sites were characterized by dissecting plants and through staining methods. Ceresa nigripectus could complete its life cycle entirely by using only alfalfa as a host. Females do not tend their broods. Eggs are laid individually and rarely 2 or 3 were found in the same slit. Eggs were located in the stems, in the nodes (in the axils of the leaves) or in the internodal space, between the epidermis and cortical tissues. The pre-ovipositional period was about 6 days, and the average duration of the egg stage was 20 days. The duration of nymphal period was variable, between 32 to 63 days, with a mean of 45 days. Two periods of high mortality were recognized, i.e., in the first instar, and during the second week of the adult stage. Longevity of adults averaged 61 days, but some individuals survived up to 202 days; females lived longer than males. In laboratory colonies, the sex ratio was about 1.3:1 females:males. All the developmental stages of the treehopper were tended by the ant Camponotus punctulatus Mayr. Data regarding behavioral aspects and new distributional information are also provided.